2019
DOI: 10.29309/tpmj/2019.26.06.3594
|View full text |Cite
|
Sign up to set email alerts
|

Students’ perception regarding skill lab training in medical education

Abstract: Introduction: Clinical skills refer to the skills required for a clinician to manage a complete patient encounter. Clinical skill laboratories provide the facility to medical students and medical staff to learn the clinical skills before applying them on patients. Objectives: To evaluate perception of medical students regarding skill lab training. Study Design: Cross -sectional study. Study Setting: Wah Medical College. Period: January 2017 to June 2017. Study Subject: Students of Final Year M.B.B.S. Sample Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
2
0
2
Order By: Relevance
“…For example, Imrani et.al. in their study evaluated the attitude of students towards this center and stated that participation in Skill Lab sessions in the preclinical years will assist students in their clinical year to achieve better overall performance, as well as better communication skills and self-esteem (1). Another study showed that the majority of students prefer participation in skill lab for learning essential clinical skills such as venous blood sampling, catheterization, endotracheal intubation, listening to respiratory sounds, genital examination, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Imrani et.al. in their study evaluated the attitude of students towards this center and stated that participation in Skill Lab sessions in the preclinical years will assist students in their clinical year to achieve better overall performance, as well as better communication skills and self-esteem (1). Another study showed that the majority of students prefer participation in skill lab for learning essential clinical skills such as venous blood sampling, catheterization, endotracheal intubation, listening to respiratory sounds, genital examination, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Mastering clinical skills is one of the essential requirements for becoming a physician and pre-clinical courses play an important role in forming these clinical skills in students. The importance of these courses is such that a Clinical Skill Training Center (CSTC) has been formed especially for this purpose, which is nowadays used for training pre-clinical skills and some of the more advanced procedures such as operating room simulation (1). The CSTC is an educational environment where students can use the available resources and the supervision of experienced faculty members to be introduced to clinical skills, train and gain experience in these skills and receive immediate feedback to resolve their mistakes and shortcomings (2).…”
Section: Introductionmentioning
confidence: 99%
“…Selain itu pada penelitian yang dilakukan Hasil ini dapat disebabkan karena sebelum pandemi pembelajaran baik pada mahasiswa preklinik dan dokter muda dilakukan secara luring, akan tetapi sejak pandemi COVID-19 terjadi di tahun 2020 pembelajaran dilakukan secara daring ataupun hybrid. Ketika pembelajaran dilakukan secara luring dokter muda memiliki tingkat kecemasan yang lebih tinggi dikarenakan terdapat banyak stressor yang dapat memicu kecemasan di lingkungan rumah sakit seperti interaksi dengan staf yang lebih senior, kekhawatiran akan salah memberikan diagnosis pasien, interaksi dengan kasus-kasus kegawatdaruratan di rumah sakit, serta harusnya untuk melakukan jaga malam yang menguras energi [11]. Hal ini berbeda dengan masa pandemi dimana untuk mencegah penyebaran COVID-19 pada dokter muda, terdapat pembatasan jumlah dokter muda yang masuk dalam sehari sehingga para dokter muda tidak perlu berjaga di rumah sakit setiap hari.…”
Section: Pembahasan Analisis Hasil Penelitianunclassified
“…Untuk mengimbangi dan mempertahankan kualitas lulusan, maka kurikulum pendidikan kedokteran disesuaikan menjadi kurikulum berbasis kompetensi (KBK) (10). Hal ini dikarenakan jurusan pendidikan kedokteran harus menghasilkan lulusan yang dapat beradaptasi dengan lingkungan terutama lingkungan kesehatan yang terus membutuhkan sumber daya yang baik (10)(11)(12).…”
Section: Pendahuluanunclassified